Pengaruh Faktor Fundamental Dan Risiko Sistematik Terhadap Harga Saham Sektor Properti Di Bursa Efek Indonesia Tahun 2008-2012 - Yunavita Uzzie Elsanti; Fitri Lukiastuti; Setyo Pantawis (Universitas Muhammadiyah Semarang, 2014)
Investing in property is included in the invesment sector which has a hogh risk because the property is very sensitive to macroeconomic conditions. Therefore property share prices in the stock market is very volatile. Fundamental analysis and systematic risk is one step that can be used before investing especially in the property sector. For this study it was established with the aim to find out and obtain empirical avidence about the fundamental and systematic risk factors that affect the stock price of the property. Fundamental factors use are NPM, ROA, ROE, EPS, DER, BVS, and Systematic Risk represented by the Beta. This study used purposive sampling to select a sample of the population of the properties listed companies on the Stock Exchange from 2008-2012. The data analysis technique used is multiple linear regression. The results showed that the only variable that ROA has a positive influence in the share price of the property, while the variable NPM, ROE, DER, EPS, BVS, and Systematic Risk does not have an influence on the stock price of the property. Adjusted R2 value in this study was 25%.Keywords : Fundamental Factors, Systematic Risk, Stock Price